Health seeking behaviour and its determinants among rural population- a cross sectional study in South India - Kumar, Hemant; Kapinakadu, Sachidananda; Anil, Manjula (International Journal Of Community Medicine And Public Health, 2019)
Background: Remedial action that a person takes to treat his or her perceived illnesses, is called health-seeking behaviour. Understanding health seeking behaviour (HSB) in a community and the factors which influence their decision, are crucial for planning a “need based” comprehensive health care programmes for the people, especially for underprovided and rural population. The objective of present study was to determine HSB and its determinants in a defined rural population. Methods: A community based cross -sectional study was conducted in rural field practice area of A. J. Institute of Medical Sciences and Research Centre, Mangalore (Karnataka) from 1st October 2017 to 31st July 2018. A total of 866 heads of households were included in the study, using universal sampling method. A pre-tested, validated questionnaire was used to collect the data. p values of <0.05 were considered significant. Results: Among 866 participants, almost all (98.03%) heads of families were males, while majority of them (35.68 %) were farmers. Further, majority (48.15%) of the households preferred to visit government hospitals for their ailments, while among those visiting private practitioners, majority of them (55.54%) preferred Allopath system of medicine. Health insurance subscription rates were found to be low (18.93%). Main determinants of HSB were observed to be cost of treatment, convenience of approach, quality of services and life threatening emergencies. Conclusions:Present study brings out higher utilization of government health care facilities among the study subjects, while cost of treatment and life threatening emergencies were the main predictors of HSB.